A theoretical study of water adsorption and dissociation on Ni(111) surface during oxidative steam reforming and water gas shift processes. Issue 2 (May 2015) - Wang, Wenju; Wang, Guoping
Abstract Density functional theory (DFT) calculations were performed to investigate the adsorption of water (H2O) on Ni(111) surface and the corresponding dehydrogenation reaction during oxidative steam reforming. The equilibrium configuration on top, bridge, and hollow (fcc and hcp) site was determined by relaxation of the system. The adsorption of H2O on top site is favorable on Ni(111) surface, while the adsorptions of OH, H and O on hollow (fcc) site is preferred. The adsorbates are adsorbed on the nickel surface due to the interaction between p orbital of adsorbates and d orbital of nickel atoms, and the interaction is manifest on the first layer than that on any others. The dehydrogenation reaction of H2O on clean and oxygen-covered nickel surface was also investigated. The results show that the dissociation energy of H atom is 72.95 kJ mol−1 on clean nickel surface. While dissociation energy decreases to 69.86 kJ mol−1 with the aid of pre-adsorbed O atom (Oads). These phenomena indicate that the energy barrier of dehydrogenation on the pre-covered oxygen nickel surface is lower and Oads can promote the dehydrogenation of H2O.